Degas. - Forty, Sandra (TAJ Books International, 2013)
Edgar Degas began as a classical painter of genre history scenes and died as one of the greatest and most innovative names in French art--although as with so many other artists, he did not receive a great deal of recognition in his lifetime. Along the way his style changed completely from strict academic formalism to near-abstract scenes of contemporary Parisian life. His primary subject was the human form, especially that of women, and he also loved the vibrancy of horse racing. Degas is usually labeled an Impressionist because he was friendly with many of the Impressionist painters and was a founder of the Impressionist movement, but he actually rejected the characterization and referred to his style as "realism." Unlike the Impressionists, he painted only in a studio, forsaking the Impressionists' embrace of painting en plein air. Degas first went to the Paris Opera to see the ballet when he was over 40 years old, and for the next 30 years made the dancers his principal subjects and grand obsession. He is particularly remembered for his paintings of young ballet dancers. He rarely shows the public performance of the dance, instead depicting rehearsals, dance classes, costume fittings, and the long waits between dancing. His main intrigue and desire was to show the strain behind the perfection.